Intracardiac Lateral Tunnel Fontan by using Right Atrial Wall - Islam, Md Zahidul; Rahim, AM Asif; Hasan, Kazi Abul; Ahsan, Syed Imtiaz (Cardiovascular Journal, 2016)
The Fontan procedure is a palliative surgical procedure used in children with complex congenital heart defects. It involves diverting the venous blood from the right atrium to the pulmonary arteries without passing through the morphologic right ventricle. A 23 years old adult male from Noakhali admitted with the diagnosis of transposition of great arteries (D-TGA) with large perimembranous ventricular septal defect (PM VSD) with severe pulmonary stenosis (PS) and single ventricle morphology in National Institute of Cardiovascular Disease (NICVD), Dhaka .He underwent Intracardiac lateral tunnel Fontan by using right atrial wall. Patient recovered uneventfully in his early postoperative period. The lateral tunnel Fontan procedure results in excellent long-term outcome even when used in patients with diverse anatomic diagnoses. The incidence of atrial tachyarrhythmia is low and mainly depends on the underlying cardiac morphology and preoperative arrhythmia. The good long-term outcome after an intracardiac lateral tunnel Fontan procedure should serve as a basis for comparison with other surgical alternatives. But using right atrial wall as a buffle is rare and done first time in Bangladesh. Cardiovasc. j. 2016; 9(1): 68-72